1983
DOI: 10.1111/j.1432-1033.1983.tb07815.x
|View full text |Cite
|
Sign up to set email alerts
|

Brown‐adipose‐tissue mitochondria: the regulation of the 32 000‐Mr uncoupling protein by fatty acids and purine nucleotides

Abstract: The increased proton permeability induced by the addition of a synthetic proton translocator to non‐respiring hamster brown‐fat mitochondria is unaffected by purine nucleotide addition. In contrast the permeability induced by fatty acids is inhibited by nucleotide, indicating that fatty acids act at the 32000‐Mr uncoupling protein. Fatty acids lower the affinity of nucleotide binding to the 32000‐Mr protein, but not sufficiently to explain their uncoupling action. The sensitivity of the fatty acid modulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(104 citation statements)
references
References 24 publications
7
94
1
1
Order By: Relevance
“…According to Rial et al [30] and Klingenberg [16], not only wide-spread natural fatty acids like palmitate, stearate and oleate, but also carboxylic acids with a shorter hydrocarbon chain are still competent (but at higher concentrations) in activating the thermogenin-mediated H + conductance. Recently Garlid showed [27] that hexane suifonate can substitute for palmitate in activating the H ~ conductance via thermogenin, the half-maximal concentration of hexane sulfonate being more than 10 ~ times higher than that of palmitate.…”
Section: Fatty Acid Circuit Hypothesismentioning
confidence: 99%
“…According to Rial et al [30] and Klingenberg [16], not only wide-spread natural fatty acids like palmitate, stearate and oleate, but also carboxylic acids with a shorter hydrocarbon chain are still competent (but at higher concentrations) in activating the thermogenin-mediated H + conductance. Recently Garlid showed [27] that hexane suifonate can substitute for palmitate in activating the H ~ conductance via thermogenin, the half-maximal concentration of hexane sulfonate being more than 10 ~ times higher than that of palmitate.…”
Section: Fatty Acid Circuit Hypothesismentioning
confidence: 99%
“…Apart from other types of mitochondria they possess the uncoupling protein (UP), a unique proton translocator [2,3], converting A/~H + into heat. H + fluxes through the UP are inhibited by purine nucleotides [4][5][6][7][8] and activated by fatty acids [3,[8][9][10]. Both regulatory mechanisms were also demonstrated in a reconstituted system [3], but the activation by fatty acids was disputed in another laboratory [2].…”
Section: Introductionmentioning
confidence: 99%
“…The stronger uncoupling effect of FA in BAT mitochondria clearly reflects activation of H ÷ transport through UP and correlates with the exclusive occurrence of UP in BAT [9,10]. In our work we used a controlled removal of endogenous fatty acid from BAT mitochondria by a carnitine cycle [8,9,[18][19][20] in order to estimate the interrelationship between effects of purine nucleotides and fatty acids on UP function.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that UP exists in the membrane as a functional dimer [15, 251 containing a single nucleotide-binding site on the cytosolic surface [19,26,271 of the inner mitochondrial membrane and that both H ' and C1-are transported via a single channel in UP [20,281. However, a lack of any competition between H + and C1-transport, occurring simultaneously in KCl, indicated that two distinct and independent pathways for H ' and C1-translocation via UP might exist [29].…”
mentioning
confidence: 99%